1970
DOI: 10.1037/h0029204
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in cheating during a temptation period when confronting failure.

Abstract: The effects of social desirability, need for social approval, self-satisfaction, and sex differences on the tendency to cheat when confronted with failure were investigated. Subjects were placed in a temptation situation in which they failed to meet social norms unless they cheated during a temptation period in which it appeared that cheating would be undetected. The two groups that were found to demonstrate the most extensive cheating were women scoring high on the self-satisfaction measure and subjects scori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 8 publications
3
38
0
2
Order By: Relevance
“…Also, research in other countries, such as South Africa, has shown a similar sex difference, with male students cheating more than female students (Burns, Davis, Hoshino, & Miller, 1998). From a cultural point of view, however, it is noteworthy that the results pertaining to sex differences on academic dishonesty have not been consistent in research with American students in that some studies have found that American female students cheat as much as or more so than American male students (Graham et al, 1994;Jacobson et al, 1970;Karabenick & Srull, 1978). Also, cross-cultural research has indicated that Japanese female students report engaging in more cheating than Japanese male students (Burns et al, 1998).…”
Section: Sex Differencesmentioning
confidence: 91%
See 1 more Smart Citation
“…Also, research in other countries, such as South Africa, has shown a similar sex difference, with male students cheating more than female students (Burns, Davis, Hoshino, & Miller, 1998). From a cultural point of view, however, it is noteworthy that the results pertaining to sex differences on academic dishonesty have not been consistent in research with American students in that some studies have found that American female students cheat as much as or more so than American male students (Graham et al, 1994;Jacobson et al, 1970;Karabenick & Srull, 1978). Also, cross-cultural research has indicated that Japanese female students report engaging in more cheating than Japanese male students (Burns et al, 1998).…”
Section: Sex Differencesmentioning
confidence: 91%
“…Others have found that female students engage in more academic dishonesty than male students (e.g., Graham et al, 1994;Jacobson, Berger, & Millham, 1970). Most studies, however, find that male students engage in more cheating than female students (e.g., Baird, 1980;Cochran et al, 1998;Davis et al, 1992;Hetherington & Feldman, 1964;Kelly & Worrell, 1978;Roth & McCabe, 1995).…”
Section: Correlates Of Cheating Behaviormentioning
confidence: 92%
“…As a result, high need for approval is associated with generally high impression management (Millham & Kellog, 1980). For example, Jacobson, Berger, and Millham (1970) found that people with a high need for approval cheated more extensively during a temptation period when confronting failure. People who self-monitor have an acute sensitivity to the cues in a situation that indicate what expression or selfpresentation is appropriate and what is not (Snyder, 1974).…”
Section: Personality Traitsmentioning
confidence: 99%
“…Evidence on the extent to which IM is associated with cheating is equivocal at best. Although there are studies that associate IM with cheating (Lobel & Levanon, 1988;Millham, 1974), there appears to be stronger evidence that an IM-cheating link is either negative (Kashy & DePaulo, 1996;Lanyon & Drotar, 1968) or simply nonexistent (Eid & Diener, 2006;Jacobson, Berger, & Millham, 1970;Schmitt et al, 2003;H.L. Smith, 1997).…”
Section: Scope Of the Present Reviewmentioning
confidence: 99%